Antibiofilm and Anti-Quorum Sensing Potential of Safely-Synthesized Hydrated Zirconium Oxide-Coated Alginate Beads against Some Pathogenic Bacteria - Alfred Ngenge Tamfu; Yasemin Ispirli Dogaç; Ozgur Ceylan; Andreea Botezatu Dediu; Selahattin Bozkurt; Rodica Mihaela Dinica (Journal of Chemistry)
Water is essential to life, but access to uncontaminated water remains a global challenge. Metal oxides possess particular characteristics required for removing heavy metals, inorganic and organic pollutants from wastewater as well as inhibiting microorganisms. Zirconium oxide and alginate which are nontoxic materials were used to synthesize hydrated zirconium oxide-alginate coated materials, ZAB-1 (1.5% alginate) and ZAB-2 (2.0% alginate). FT-IR was used to characterize the functional groups while surface morphology was characterized using SEM. XRD was used to characterize the material structure of the resulting composite. Against Chromobacterium violaceum CV12472, minimal inhibitory concentrations (MICs) were 0.625 mg/mL for ZAB-1 and ZAB-2 while against C. violaceum CV026, the MIC values were 0.625 mg/mL and 1.25 mg/mL for ZAB-1 and ZAB-2, respectively. At MIC and sub-MIC concentrations, the synthesized beads inhibited the production of violacein in C. violaceum CV12472 and C. violaceum CV026, indicating that they can reduce QS-mediated virulence factors in bacteria. Antimicrobial activity was evaluated against Staphylococcus aureus, Enterococcus faecalis, Listeria monocytogenes, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi, Candida albicans, and Candida tropicalis, and MIC values ranged from 1.25 mg/mL to 10 mg/mL. Biofilm inhibition percentages were relatively high against S. aureus, E. coli, and C. albicans. It is observed that the increase in the alginate amount from 1.5% to 2.0% improves the antimicrobial, anti-QS, and antibiofilm effects. The alginate makes the zirconium oxide particles biocompatible and easily recoverable from water after treatment. ZAB-1 and ZAB-2 materials can therefore be sustainable materials for water treatment since it can inhibit pathogenic bacteria in water and equally satisfy environmental friendliness. The synthesized particles reduced the chances for antimicrobial resistance since they disrupted QS in bacteria and eliminated biofilms, thereby preventing biofouling of microbial communities in water. Future prospects of this study involve biofiltration, that is, the use of the synthesized composite in the development of a safe and compatible biofilter for water purification.